Automated monitoring and controlling pH levels for hydroponics cultivation technique - Mohammad Farid Saaid; Ahmad Ihsan Mohd Yassin; Nooritawati Md Tahir (Institute of Advanced Engineering and Science, 2020)
A hydroponics plant can grow healthily with sufficient nutrient, temperature, light, humidity as well as pH level that is indeed vital in ensuring the plants will absorb maximum nutrient elements required. This paper presents automated monitoring and controlling pH levels for the hydroponic cultivation technique. In this study, automated monitoring and controlling of pH levels are developed specifically for the hydroponic cultivation technique. There are three main methods that involved in the development of the system namely hardware, programming and functionality test. Firstly, users need to set the maximum and minimum pH levels as required by the plant. Then, the pH sensor will monitor the real-time pH level of the water. A syringe pump that contains a pH up solution (alkaline) and a pH down solution (acid) will drip the solutions to neutralize the water content if the water pH level is not within the stated ranges as set by the user. Results showed that the automated monitoring and controlling pH levels were successfully developed and functionality was tested and confirmed as desired. The syringe pumps responded perfectly upon changes of the water pH value based on the validation done that showed 100% accuracy of the syringe pump responds.